2018
DOI: 10.1101/338582
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

H3K9me3 is Required for Inheritance of Small RNAs that Target a Unique Subset of Newly Evolved Genes

Abstract: In Caenorhabditis elegans, RNA interference (RNAi) responses can transmit across generations via heritable small RNAs. Heritable RNAi memory is associated with Histone-3-Lysine-9 tri-methylation (H3K9me3) of the targeted genes. In other organisms, maintenance of silencing responses requires a feedforward loop between H3K9me3 and small RNAs. In C. elegans, however, we find that the effect of H3K9 methyltransferase mutants on heritable RNAi is more complex. In this paper, we show that not only that H3K9me3 is un… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…We found that hrde-1, nrde-3 and rrf-1 mutants, as well as additional mutants defective in siRNA biogenesis (rde-1, rde-4, rrf-3 and mut-16), are not required for the inheritance of the elongated morphology (figure 4). Previously, histone-H3-lysine-9 (H3K9) methylations were implicated in trans-generational inheritance of small RNAs [47][48][49][50]. H3K9 mono-and di-methylations are deposited by the MET-2 methyltransferase [51], while H3K9me3 is deposited by the SET-25 and SET-32 methyltransferases [51,52].…”
Section: (D) Progeny Of Liquid-grown Worms Are Longer Even In Mutantsmentioning
confidence: 99%
“…We found that hrde-1, nrde-3 and rrf-1 mutants, as well as additional mutants defective in siRNA biogenesis (rde-1, rde-4, rrf-3 and mut-16), are not required for the inheritance of the elongated morphology (figure 4). Previously, histone-H3-lysine-9 (H3K9) methylations were implicated in trans-generational inheritance of small RNAs [47][48][49][50]. H3K9 mono-and di-methylations are deposited by the MET-2 methyltransferase [51], while H3K9me3 is deposited by the SET-25 and SET-32 methyltransferases [51,52].…”
Section: (D) Progeny Of Liquid-grown Worms Are Longer Even In Mutantsmentioning
confidence: 99%
“…Typically, dsRNA-triggered heritable responses persist for 3-5 generations 6,7 , owing to a dedicated pathway which regulates the duration of each heritable response 7,8 . Maintenance of RNAi interference (RNAi) over generations involves specialized argonaute proteins [9][10][11] , amplification of the small RNAs by RNA-dependent RNA Polymerases 12,13 (RdRPs), and chromatin modifiers 8,[14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…How small RNAs cooperate with repressive histone PTMs in epi genetic inheritance is currently unclear 44,46,48,50 . Although the inactivation of RNAi components such as HRDE1 or NRDE2 did not affect the transmission of this H3K9me3mediated epigenetic memory 54 , very recent data argue that H3K9me3 might be required for siRNA dependent TEI that specifically targets newly evolved genes and is particularly sensitive to transgenes 55 .…”
Section: Histone Ptm Inheritance In Caenorhabditis Elegansmentioning
confidence: 98%